Quadruple fenestration aortic stent implantation combined with unilateral IBE and internal iliac artery stent implantation for complex abdominal aortic aneurysm: one case report - Zhou, Guanzhi; Ma, Huibo; Liu, Junjun; Sun, Xiaozhi; Liu, Yangshuo; Luan, Jianli; Li, Yongxin; Guo, Mingjin (Frontiers in Cardiovascular Medicine, 2023)
An abdominal aortic aneurysm is a frequently encountered clinical condition, which necessitates prompt and effective remediation to avoid rupture. Surgeons must meticulously select an appropriate method of repair and assess the long-term surgical prognosis when dealing with patients with complex abdominal aortic aneurysms. In this case report, a 74-year-old man was hospitalized due to acute abdominal pain. Upon further examination, it was discovered that he was suffering from a complex abdominal aortic aneurysm. The thoracoabdominal aorta CTA showed that the aneurysm involved both renal arteries, the part below the kidney was severely twisted, the neck of the aneurysm was short, and it was accompanied by bilateral common iliac and internal iliac aneurysms, and there were considerable thrombus attached to the vessel wall. In this case, our team used 3D technology to simulate the spatial structure of the aneurysm and comprehensively evaluate the patient's condition. Ultimately, we decided to perform a quadruple fenestration aortic stent implantation and endovascular repair of aortic aneurysm, combined with right IBE and internal iliac artery stent implantation, right internal iliac artery reconstruction, and left internal iliac artery aneurysm embolization on this patient. This is an innovative surgical method. The operation was successful and the patient recovered well after the operation.